ЕКОНОМСКА АНАЛИЗА НА ДИРЕКТНИТЕ ЕФЕКТИ НА ИНДУСТРИЈАТА ЗА ОСНОВНИ МЕТАЛИ ВО МАКЕДОНСКАТА ЕКОНОМИЈА (Yearbook - Faculty of Economics, 2018)
Scientific and professional public obviously highlight the fact that the development dynamics of each national economy is largely based on more efficient industrial system (hence strongly highlighted efforts for reindustrialization of the world economy), given the fact that the technical progress largest economic effects materialize in the framework of the industry. In this context, identifying and quantifying the role and importance of each industry to the national economy is of paramount importance in the process of designing national industrial policies. The main aim of this paper is quantitative and scientifically based assessment of basic metal industry and its role and importance for the Macedonian economy through the application of economic impact methodology based on input - output model and analysis of economic of financial indicators that measure the industry performance. Such economic assessment and analysis involves studying the direct effects (contribution to GDP, exports, employment, taxes and corporate - social responsibility) and multiplicative effects (indirect through the chain of suppliers and induced by the effect of consumption) that the industry generates in the national economy by the reproduction processes.